Barriers to Care: Improving Attendance at a Student-Run Free Psychiatry Clinic - Mause, Elizabeth; Crowther, Lauren; Munger, Emmali; Qadri, Syed (Journal of Student-Run Clinics, 2022)
Background: One-time clinic attendance and inconsistent follow-up are common in patients experiencing homelessness and those who access care in student-run free clinics (SRFCs). While mental health concerns are prevalent in this population, the consistent follow-up and longitudinal care necessary to improve patient outcomes has many barriers. The primary objective of this study was to assess and address the patient-identified barriers to attendance at a SRFC that operates out of a homeless shelter in Omaha, Nebraska. Methods: Through a survey, patients indicated if one or more barriers in a list of examples had prevented their attendance in the past. This study also ascertained if patients had social support in place and reviewed demographic information. Between September 2020 and May 2021, 14 psychiatry clinics were held bimonthly with 35 different patients during which each patient was requested to complete a survey. Of the 35 requested, 13 patients completed the survey. Results: Of the 13 patients, 62% reported at least one barrier to care. Primary barriers patients experience are forgetting appointment time (38%), feeling so poorly they don’t feel like going (31%), and having problems with transportation (31%). Although not statistically significant, there was a trend of having a case manager (OR = 0.2143, 95% confidence interval [CI] 0.0136 - 3.3698) or having at least two social support systems (OR = 0.2143, 95% CI 0.0136 - 3.3698) decreased the odds that patients would report two or more barriers to care. Conclusions: Over half of the participants reported at least one barrier to care. Although not statistically significant, there was a trend that having a case manager and social support reduced the odds of patients reporting barriers. We suspect that creating stronger relationships with patients directly through patient liaisons and strengthening relationships with case managers will improve communication and decrease no-show rates.